Clinical Application of the UK Working Party's Criteria for the Diagnosis of Atopic Dermatitis in the Chinese Population by Age Group - Wang, Li (Chin Med J (Engl), 2016)
BACKGROUND: Atopic dermatitis (AD) is a common inflammatory skin disease with an increasingly significant prevalence. The prevalence of AD depends greatly on how its diagnosis is done. The UK Working Party's diagnostic criteria for AD are simple and easy to apply without invasive laboratory tests. This study assessed the clinical utility of these criteria in China. METHODS: Data were collected from 6208 patients at 31 tertiary hospitals in 13 Chinese provinces/municipalities from March 2014 to May 2014. The agreement between the UK diagnostic criteria and the clinical records for AD was assessed by Cohen's kappa. RESULTS: The overall agreement between the UK diagnostic criteria and clinical diagnosis was fair (kappa = 0.40). A slightly better agreement was found in patients aged between 4 and 9 years (kappa = 0.48), while fair agreement was found in the group <4 years and the group ≥10 years (kappa = 0.27 and 0.39, respectively). Using the UK party's criteria as the standard, the sensitivity, specificity, positive predictive value, and negative predictive value of the clinical diagnosis of AD were 62.3%, 89.2%, 38.0%, and 95.7%, respectively. CONCLUSIONS: Our study indicates a modest ability among Chinese dermatologists to apply the UK Working Party's diagnostic criteria for AD, especially in patients aged <4 years and ≥10 years. Since there is no gold standard for AD diagnosis, it is important to determine how AD is identified when evaluating a diagnostic tool.